Implementasi Kebijakan Sabilulungan Sistem Penilaian Kinerja Pegawai (SASIKAP) di Lingkungan Pemerintah Kabupaten Bandung - Marlian, Shela; Sari, Deasy Silvya (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2020)
The urgency of performance assessment in ASN management has led to innovations in employee performance assessment based on information technology. This article aims to describe the implementation condition of Sabilulungan Employee Performance Assessment System (SASIKAP) policy as a technology-based performance assessment instrument for the State Civil Service Apparatus (ASN), from various aspects such as policy, implementation and the environment. This is related to the phenomenon that there are still employees who do not fill out the application themselves, the inconsistency between individual work targets and organizational work targets and the lack of optimal performance monitoring and appraisal processes by appraisers. The authors use a descriptive qualitative method and examines the four locus of Regional Apparatus which have different characteristics and conditions in Bandung Regency Government. The authors found that: SASIKAP policy standards and objectives have been listed in the form of Bandung Regent Regulation Number 18 of 2019 and its technical guidelines; Human resources and infrastructure in Bandung Regency Government has supported the operationalization of SASIKAP; Communication between organizations and implementation activities is running properly; there is an executing agent that makes SASIKAP easier to operate; The economic, social and political environment supports the implementation of SASIKAP policies; and The implementation of SASIKAP policy has generally been responded positively by ASN within the Bandung Regency Government.